Super vegetables - Mohd. Fareq, Abd. Malek, Dr.; Nur Athirah, Mat Lazim; Muhammad Ezanuddin, Abdul Aziz (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.